PERAN AKTIF SAINS WARGA UNTUK AKSELERASI PEROLEHAN DATA KUPU-KUPU DI INDONESIA TERKAIT PROJECT BIFA-GBIF - Djunijanti Peggie; Muhammad Rasyidi; Imti Yazil Wafa; Karyadi Baskoro (BERITA BIOLOGI, 2021)
Citizen science participation in the scope of biodiversity data acquisition has increased globally. Data on the occurrence of butterflies are usually obtained through specimen inventories, which are costly and labor intensive. Without compromising the importance of specimens, data acquisition on the occurrence of butterflies from various areas in Indonesia through butterfly photos can be pursued through the contribution of citizen science. This initiative was carried out as part of the BIFA-GBIF project. The involvement of citizen science is very effective in increasing the acquisition of data on the occurrence of various butterfly species. More than 1,000 photographs of butterflies were received from 26 persons contributing to the initiative, and 744 entries have been processed resulting in records of 197 butterfly species. This initiative opens up more opportunities in the future.ABSTRAKPartisipasi sains warga dalam lingkup perolehan data biodiversitas telah meningkat secara global. Data keberadaan kupu-kupu biasanya diperoleh melalui inventarisasi spesimen, yang membutuhkan banyak biaya dan tenaga. Tanpa mengurangi nilai penting spesimen, perolehan data keberadaan kupu-kupu dari berbagai area di Indonesia melalui foto kupu-kupu dapat diupayakan melalui kontribusi sains warga. Inisiatif ini dilakukan sebagai bagian dari project BIFA-GBIF. Keterlibatan sains warga sangat efektif dalam meningkatkan perolehan data keberadaan berbagai spesies kupu-kupu. Lebih dari 1.000 foto kupu-kupu telah diterima dari 26 orang yang berkontribusi dalam inisiatif ini, dan 744 entry telah diproses yang menghasilkan data rekaman 197 spesies kupu-kupu. Inisiatif ini membuka lebih banyak peluang ke depannya.